Capital drug laws in Asia - Chan, Wing Cheong; Satō, Mai; Hor, Michael (Cambridge University Press, 2025)
"Provides an overview on the use of punitive drug policies in Asia and offers a comparative perspective on the implications of the "war on drugs" in the region characterised by disproportionate penalties, denial of legal rights, exploding prison populations, and unquestioning faith in the deterrent effects of the death penalty"--